Penetapan Parameter Standar Simplisia dan Ekstrak Etanol Daun Ganitri (Elaeocarpus serratus L.) - Naelaz Zukhruf Wakhidatul Kiromah; Sinta Wahyu Septiani; Wahyu Rahmatulloh; Ari Purnomo Aji (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2020)
Ceylon olive (Elaeocarpus serratus L.) leaves have shown many pharmacological effects. Standardization of crude drug and extract needs to be conducted to assure the quality of the said material and further to support the pharmacological, pharmacokinetics, and toxicity effects. Standardization of Ceylon olive leaf extract is carried out to determine the standard parameters of crude drug and ethanolic extract of Ceylon olive leaves. Determination of the quality standard of crude drug and extract includes specific and non-specific parameters. The extract was obtained from a 70% ethanol maceration method with a yield of 16.02%. Macroscopic observations showed crude drugs of Ceylon olive leaves occurred as green in color, lanceolate leaves, 2-12 mm stems, and jagged leaves not deep, black spots, 10-15 side leaf bones, 6-18 cm long and 2-6 cm wide. Organoleptic of ethanolic extract of Ceylon olive showed thick consistency, blackish-brown colored, with a distinctive odor and a bitter taste. The water-soluble extractive value in crude drugs and extract was 16.48 and 51.54%, while the ethanol-soluble extractive value was 23.17 and 53.67%, respectively. The extract contained tannins, flavonoids, terpenoids, and saponins. Moisture content in the crude drugs and extracts was 22.09 and 25.53%. Total ash content in crude drugs and extracts was 33.53 and 30.62%, while their acid-insoluble ash content was 15.94 and 10.06%, respectively. Loss on drying of the crude drugs and extracts was 20.52 and 23.84% respectively. As the standard parameters of crude drugs and ethanolic extract of Ceylon olive leaves are not yet included in any formal monograph in Indonesia, the values of parameters reported in this study should be used as the reference of the standard quality parameter for those materials.